Geometric Analysis of the Bilobed Flap for Nasal Reconstruction Surgery. (June 2021) - Henick, Daniel; Ampem-Darko, Kelvin K.; Sayegh, Farah; Sanati-Mezrahi, Paymon; Bhatt, Mehul; Taub, Peter J.
Background: Reconstruction of the nose can be difficult due to its complex anatomical features. In 1989, Zitelli described a modified version of the bilobed flap design technique using 45° and 90° angles to improve nasal reconstructions. While the bilobed flap is still frequently referenced in scholarly literature, there seems to be inconsistency in preoperative flap design; these deviations can lead to suboptimal outcomes. The authors aim to illustrate the variability in bilobed flap execution and provide guidelines in preoperative design to improve consistency.Methods: A geometrically-based approach was used to characterize the inconsistency of bilobed repair technique. The pre-operative design images from fifteen scholarly articles were analyzed via a series of measurements and computations to quantify the angle of rotation and dimensions for the primary and secondary lobes. The "Error Quotient" was a calculated ratio that objectively measured the extent to which a bilobed design deviated from Zitelli's specifications.Results: There was a noticeable variability in the design of both the primary and secondary lobes. Bilobed designs with smaller angles of rotation, particularly of the first lobe, were associated with higher Error Quotients and greater amounts of deviation from Zitelli's design. Designs with the smallest Error Quotients had a primary lobe rotation that approached 45°.Conclusion: Consistency of application of the bilobed flap should be established to allow for optimal results, particularly with emphasis on design of the primary lobe. This can be accomplished by including a disposable protractor and marker in their sterile kit to measure a 45° rotation.